2023
DOI: 10.5847/wjem.j.1920-8642.2023.021
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model for patients with post-extubation dysphagia

Abstract: BACKGROUND: Swallowing disorder is a common clinical symptom that can lead to a series of complications, including aspiration, aspiration pneumonia, and malnutrition. This study aimed to investigate risk factors of post-extubation dysphagia (PED) in intensive care unit (ICU) patients with endotracheal intubation, and to develop a risk-predictive model for PED, which could serve as an assessment tool for the prevention and control of PED.METHODS: Patients retrospectively selected from June to December 2021 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…44 Moreover, tube-fed nutrition causes the throat reflex to become passive, which can further worsen patients' poor swallowing function. 30 It has been found that for each hour of prolonged time the gastric tube is indwelled, and the incidence of PED increases by 33.52 times. 45 Moreover, aspiration of gastric contents is common in critically ill gastric feeding patients, and it is a major risk factor for pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…44 Moreover, tube-fed nutrition causes the throat reflex to become passive, which can further worsen patients' poor swallowing function. 30 It has been found that for each hour of prolonged time the gastric tube is indwelled, and the incidence of PED increases by 33.52 times. 45 Moreover, aspiration of gastric contents is common in critically ill gastric feeding patients, and it is a major risk factor for pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the nine included models were developed by logistic regression, 1,[19][20][21][22][30][31][32] and one was developed using the generalized additive model. 29 Of the nine models that were included, only two underwent internal validation, 19,31 while two others were subjected to external validation.…”
Section: Characteristics Of the Prediction Modelsmentioning
confidence: 99%
See 3 more Smart Citations